An Empirical Study of the Development of Information and Communication Technology in Hungary - Peter Sasvari (Theory, Methodology, Practice / Club of Economics in Miskolc, 2010)
As I could not find a reliable mathematical and statistical method for studying the effect of information communication technology on businesses in the literature, I proposed a new research and analysis method that I also used to study the Hungarian economic sectors. An essential question for enterprises is what factors have an effect on their net income. First, I studied the potential indicators related to economic sectors, then I compared those indicators to the net income of the enterprises surveyed. The data resulting from this comparison showed that the growing penetration of electronic marketpalces contributed to the change in the net income of enterprises in various Hungarian economic sectors to the extent of 37%. Among all the potential indicators, only the indicator of electronic marketplaces has a direct influence on the net income of enterprises. However, the effect of electronic presence is also significant as it has a huge effect on the potential indicator of electronic marketplaces. It was practical to determine two clusters based on the potential indicators. Eight economic sectors have been placed in the first, while five sectors have been placed in the second cluster. Only the money which is spent on professional training has a more significant effect on what cluster a sector belongs to.
Keywords: C10; M15; 330; information society; information and communication technology; economic branch; ICT; electronic presence; electronic marketplace